ECM Substrates Impact RNAi Localization at Adherens Junctions of Colon Epithelial Cells - Amanda C. Daulagala; Antonis Kourtidis (Cells, 2022)
The extracellular matrix (ECM) plays crucial roles in tissue homeostasis. Abnormalities in ECM composition are associated with pathological conditions, such as fibrosis and cancer. These ECM alterations are sensed by the epithelium and can influence its behavior through crosstalk with other mechanosensitive complexes, including the adherens junctions (AJs). We have previously shown that the AJs, through their component PLEKHA7, recruit the RNAi machinery to regulate miRNA levels and function. We have particularly shown that the junctional localization of RNAi components is critical for their function. Here, we investigated whether different ECM substrates can influence the junctional localization of RNAi complexes. To do this, we plated colon epithelial Caco2 cells on four key ECM substrates found in the colon under normal or pathogenic conditions, namely laminin, fibronectin, collagen I, and collagen IV, and we examined the subcellular distribution of PLEKHA7, and of the key RNAi components AGO2 and DROSHA. Fibronectin and collagen I negatively impacted the junctional localization of PLEKHA7, AGO2, and DROSHA when compared to laminin. Furthermore, fibronectin, collagen I, and collagen IV disrupted interactions of AGO2 and DROSHA with their essential partners GW182 and DGCR8, respectively, both at AJs and throughout the cell. Combinations of all substrates with fibronectin also negatively impacted junctional localization of PLEKHA7 and AGO2. Additionally, collagen I triggered accumulation of DROSHA at tri-cellular junctions, while both collagen I and collagen IV resulted in DROSHA accumulation at basal areas of cell–cell contact. Altogether, fibronectin and collagens I and IV, which are elevated in the stroma of fibrotic and cancerous tissues, altered localization patterns and disrupted complex formation of PLEKHA7 and RNAi components. Combined with our prior studies showing that apical junctional localization of the PLEKHA7-RNAi complex is critical for regulating tumor-suppressing miRNAs, this work points to a yet unstudied mechanism that could contribute to epithelial cell transformation.